2007
DOI: 10.3137/ao.450404
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal variability in a mid‐latitude ocean basin subject to periodic wind forcing

Abstract: The mid-latitude ocean's response to time-dependent zonal wind-stress forcing is studied using a reduced-gravity, 1.5-layer, shallow-water IntroductionThe wind-driven, basin-scale circulation in the mid-latitude upper ocean exhibits variability on different time scales. This variability could be due to changes in the external atmospheric forcing or to the system's intrinsic instability and nonlinearity. The latter explanation was first put forward by Veronis (1963Veronis ( , 1966, but the former has enjoyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…Still, the statistical evidence of equivalent-barotropic behavior in this region is entirely consistent with the gyremode hypothesis, such as confirmed by several studies with more or less idealized double-gyre ocean models (Jiang et al 1995;Speich et al 1995;Simonnet and Dijkstra 2002;Simonnet et al 2003aSimonnet et al ,b, 2005Sushama et al 2007). Across a hierarchy of models -from simple rectangular-shaped ocean basins and 1.5-layer reducedgravity models (Jiang et al 1995;Speich et al 1995;Chang et al 2001;Simonnet et al 2003a) to more realistic North Atlantic-basin shapes, several layers and eddypermitting resolutions (Simonnet et al 2003b(Simonnet et al , 2005 -it was found that the idealized double-gyre flow becomes unstable to two types of barotropic modes: basin modes and gyre modes.…”
Section: B Discussionsupporting
confidence: 65%
“…Still, the statistical evidence of equivalent-barotropic behavior in this region is entirely consistent with the gyremode hypothesis, such as confirmed by several studies with more or less idealized double-gyre ocean models (Jiang et al 1995;Speich et al 1995;Simonnet and Dijkstra 2002;Simonnet et al 2003aSimonnet et al ,b, 2005Sushama et al 2007). Across a hierarchy of models -from simple rectangular-shaped ocean basins and 1.5-layer reducedgravity models (Jiang et al 1995;Speich et al 1995;Chang et al 2001;Simonnet et al 2003a) to more realistic North Atlantic-basin shapes, several layers and eddypermitting resolutions (Simonnet et al 2003b(Simonnet et al , 2005 -it was found that the idealized double-gyre flow becomes unstable to two types of barotropic modes: basin modes and gyre modes.…”
Section: B Discussionsupporting
confidence: 65%
“…The domain extends further northward than southward, as our research is directed towards studying the SC and NBC, ranging within the most energetic structures in the world's oceans and both occurring north of the Equator. The model is comparable to those used in idealized configuration to study mid-latitude gyres (see, e.g., Jiang et al, 1995;Sushama et al, 2007;Speich et al, 1995) and low latitude WBCs (see, e.g., Edwards and Pedlosky, 1998a;Edwards and Pedlosky, 1998b;Fox-Kemper, 2005). A Cartesian grid is used and the Coriolis parameter varies linearly with latitude; this geometry is usually referred to as the equatorial β-plane.…”
Section: The Physical Problem Consideredmentioning
confidence: 67%
“…The coarse resolution in space and time of satellite data do not allow for a detailed study of these small-scale structures. Such flanking vortices are also present in the laboratory experiments of geophysical fluid dynamics (see, e.g., Van Heijst and Flor, 1989) and are also clearly visible in fine-resolution realistic simulations of the ocean dynamics.…”
Section: Introductionmentioning
confidence: 79%
“…The gyre mode was shown to be robust with respect to forcing by the seasonal cycle in wind stress (Sushama et al 2007) and had been found in a century of SST data for the North Atlantic (Moron et al 1998). Several other authors, going back to Veronis (1963Veronis ( , 1966 Further evidence that the 7-8-yr atmospheric mode is indeed induced by the neardecadal oscillations of the Gulf Stream front in the CHR and GBR regions is provided by three additional experiments.…”
Section: B Discussionmentioning
confidence: 91%